Telecommunications : a connected world. - CAIRNCROSS, Frances (1997)
Reports that the telecommunications revolution, driven by liberalization and the Internet, will change the way people live and work. Reviews changes that have already taken place, and reviews future changes : in competition and regulation, and in the technologies developing at such breakneck speed.